Oral manifestations and diabetes - Veiga, Nélio Jorge (2021)
The diabetic patient is subjected to a series of systemic complications and is more prone to develop other types of pathologies. This is equally applied to the oral cavity. This revision article aims to analyze some of the possible oral manifestations and complication derived from diabetes. Concomitantly it is also pretended to know why these complications and more related to these patients, as well as to observe the differences between the pathogenesis and severity of oral pathologies among diabetics and non-diabetics.